Distribution scheme of antituberculosis drug resistance among HIV patients in a referral centre over 10 years. (December 2017) - Baghaei, Parvaneh; Tabarsi, Payam; Moniri, Afshin; Marjani, Majid; Farnia, Parissa; Jabbehdari, Sayena; Velayati, Ali Akbar
Highlights: The pattern of antituberculosis drug resistance in HIV patients should be determined. A proper regimen based on resistance improves successful treatment outcomes. Multidrug-resistant TB increases mortality in HIV patients. Abstract: Objectives: Antituberculosis drug resistance is increasing among tuberculosis (TB) patients globally, particularly in those who are human immunodeficiency virus (HIV)-positive. The aim of this study was to determine the pattern of anti-TB drug resistance in these patients in an effort to improve successful treatment outcomes with a proper regimen. Methods: A cross-sectional study was conducted on adult TB/HIV co-infected patients from 2005–2015. The pattern of anti-TB drug resistance was evaluated among HIV-positive patients with and without a history of TB treatment. Categorisation was made as follows: isoniazid (INH)-resistant; rifampicin (RIF)-resistant; or multidrug-resistant (MDR). Results: A total of 52 patients were enrolled in this study (median age 38 years). Among the 52 patients, 18 (34.6%) were MDR-TB patients and the rest were monoresistant TB (resistant either to INH or RIF). INH resistance was the most common resistance pattern (36.5%) noted among patients and was significantly associated with new TB cases (69% vs. 31%; P  = 0.01). During TB treatment, 3/48 patients (6.3%) failed treatment and 11/48 (22.9%) died. Patients with MDR-TB were more likely to die during treatment (44.4% vs. 10%; P  = 0.011). Conclusions: Any drug resistance in previously treated TB cases among HIV-infected patients remains high. The risk of death is increasing in MDR-TB/HIV co-infected patients.